Actualización del tratamiento de las Anemias Nutricionales en el lactante y el preescolar. - Guevara Toapanta, Joselyne Esthefanny (2024)
Nutritional anemia in children and preschoolers constitutes one of the leading public health concerns on a global scale due to its high incidence and its adverse impact on child development, particularly in cognitive and physical aspects. This bibliographic analysis examines the most recent scientific evidence regarding treatments for nutritional anemia in children under five years old, with particular attention to the efficacy of pharmacological and non-pharmacological interventions. It used a qualitative and retrospective cross-sectional approach, applying rigorous inclusion and exclusion criteria in the selection of documents. The study focused on articles published in the last five years in open-access databases such as Google Scholar, Dialnet, and Scielo. The researcher selected the articles focused on the risk factors, clinical manifestations, and various therapeutic strategies for nutritional anemia in the pediatric population. The findings underscore the effectiveness of iron and folic acid supplementation as essential pharmacological interventions to reduce the incidence of anemia in this population. They also highlighted the relevance of nonpharmacological tactics, such as food fortification, promoting an iron-rich diet through exclusive breastfeeding, and consuming heme iron-rich foods like meats and leafy green vegetables. These procedures help reduce anemia and prevent acute and chronic complications in child development. The research underscores the urgent need to strengthen public health programs to prevent and treat nutritional anemia in children and preschool students. The examined evidence indicates that early diagnosis, in conjunction with the implementation of appropriate interventions, can reduce the likelihood of complications and optimize the quality of life of affected children.